2020
DOI: 10.1002/jcp.30129
|View full text |Cite
|
Sign up to set email alerts
|

miR‐375 induces adipogenesis through targeting Erk1 in pancreatic duct cells under the influence of sodium palmitate

Abstract: The goal of this study was to research long‐term saturated fatty acid overexposure that can induce differentiation of pancreatic duct cells into adipocytes and also into β‐cells. The important findings can be summarized as follows: (i) adipogenesis and early stage β‐cell differentiation were stimulated in duct cells under lipotoxicity and glucolipotoxicity conditions, (ii) miR‐375 expression was upregulated while its target Erk1 was downregulated and miR‐375 inhibitor upregulated Erk1 while expression of adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Reports also indicate signs of dedifferentiation and loss of function in pancreatic islet β-cells in HFD mice [58] . Excessive saturated fatty acids may induce differentiation of pancreatic ductal cells into fat cells, leading to increased fat accumulation [59] . Currently, foundational reports on the pathogenic mechanism of NAFPD are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Reports also indicate signs of dedifferentiation and loss of function in pancreatic islet β-cells in HFD mice [58] . Excessive saturated fatty acids may induce differentiation of pancreatic ductal cells into fat cells, leading to increased fat accumulation [59] . Currently, foundational reports on the pathogenic mechanism of NAFPD are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Gezginci-Oktayoglu et al . 50 reported that reducing miR-375 expression improved Erk1 expression in ARIP cells, and suppression of miR-375 suppressed the expression of the adipogenesis markers PPAR2, LPL, GLUT4, and leptin. Kraus et al .…”
Section: Discussionmentioning
confidence: 99%
“…Long-term overexposure to saturated FA may cause the differentiation of ductal cells into adipocytes or βcells. 181 Additionally, lipotoxic stimulus (long-term high concentration of FAs) can evoke insulin production in ductal cells. Furthermore, rat pancreatic ductal cell line treatment with palmitate-induced fat accumulation and leptin release.…”
Section: Er Stress and Autophagymentioning
confidence: 99%
“…Furthermore, rat pancreatic ductal cell line treatment with palmitate-induced fat accumulation and leptin release. Gezginci-Oktayoglu et al 181 demonstrated that the suppression of Erk1 during saturated FA treatment can be the background mechanism for ductal cell adipogenesis. A high-fat diet induces TG and FFA elevation in the serum of experimental animals, 182,183 and it can affect pancreatic ductal function.…”
Section: Er Stress and Autophagymentioning
confidence: 99%
See 1 more Smart Citation